Digital Marketing Strategy in the Era of Social Media: Analysis of Influencing Factors Superiority Competitive Startup Companies - Novrizal; Rachman, Zacky (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This qualitative literature review explores the role of digital marketing strategies in the social media era and their influence on the competitive advantage of startup companies. The study identifies key factors such as customer responsiveness, service quality, branding, and profitability as crucial elements for enhancing competitive advantage. Social media platforms enable startups to interact with customers more personally and directly, thereby increasing customer satisfaction and loyalty. Moreover, social media facilitates effective brand building and optimization of marketing strategies to increase profitability. Despite the valuable insights, the study is limited by its reliance on secondary data and focus on recent literature, which may not fully capture the rapidly evolving dynamics of social media. Future research should include empirical studies to provide deeper contextual understanding and explore emerging technologies and trends in social media marketing.